Pictorial Involvement. Providing access to philosophical texts via visualization through artistic practice - Reichl, Veronika; Keitsch, Maria Martina (FormAkademisk, 2013)
Theory dissemination in design can be labelled with what Rittel and Webber called a “wicked problem”. Design educators do not only struggle with the vague ontology of their discipline, but also with the fact that basic conjectures are seldom made explicit, which impedes possibilities for teaching design theory to students. This article addresses the question of how to facilitate theoretical understanding in design with the help of visualization through artistic practice. Following the introduction, which provides reasons for teaching philosophy in design at any rate, the second section presents features of a philosophy introduction course at the Oslo School of Architecture and Design (AHO). Section three introduces an experimental project on visualization through artistic practice conducted in this course in 2010. Section four presents project results by evaluating the students’ experiences. Conclusively, section five discusses benefits and challenges of this type of visualization for understanding theory in design. Results are meant to contribute to theory dissemination in the design disciplines.